2015
DOI: 10.1590/s0034-8910.2015049005822
|View full text |Cite
|
Sign up to set email alerts
|

Gender in the allocation of organs in kidney transplants: meta-analysis

Abstract: OBJECTIVE To analyze whether gender influence survival results of kidney transplant grafts and patients.METHODS Systematic review with meta-analysis of cohort studies available on Medline (PubMed), LILACS, CENTRAL, and Embase databases, including manual searching and in the grey literature. The selection of studies and the collection of data were conducted twice by independent reviewers, and disagreements were settled by a third reviewer. Graft and patient survival rates were evaluated as effectiveness measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
3
4
0
2
Order By: Relevance
“…This result has been observed in many subsequent studies [61][62][63]. It is considered that kidney allograft survival is better in a maledonor to a male-recipient [64,65]. Many factors could be involved in these sex differences.…”
Section: Renal Transplantationsupporting
confidence: 59%
“…This result has been observed in many subsequent studies [61][62][63]. It is considered that kidney allograft survival is better in a maledonor to a male-recipient [64,65]. Many factors could be involved in these sex differences.…”
Section: Renal Transplantationsupporting
confidence: 59%
“…6,20 Male-donor kidneys are believed to offer superior graft survival due to a greater nephron mass than female-donor kidneys. 22,23,[38][39][40][41] Indeed, prior studies concluded that male recipients of female-donor kidneys have poorer graft survival than all other recipient-donor sex combinations. [38][39][40][41] We do not dispute the validity of this conclusion in populations dominated by recipients .45 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Gender did not influence graft survival in our study. However recent studies have suggested men have a higher risk of graft loss compared with women in the long term (11,(36)(37)(38) .…”
Section: Discussionmentioning
confidence: 99%